Thiolation and Cell‐Penetrating Peptide Surface Functionalization of Porous Silicon Nanoparticles for Oral Delivery of Insulin. (18th April 2016) - Shrestha, Neha; Araújo, Francisca; Shahbazi, Mohammad‐Ali; Mäkilä, Ermei; Gomes, Maria João; Herranz‐Blanco, Bárbara; Lindgren, Rici; Granroth, Sari; Kukk, Edwin; Salonen, Jarno; Hirvonen, Jouni; Sarmento, Bruno; et al.
Abstract : During the last decades, advanced oral delivery systems to enhance the intestinal absorption of widely applicable proteins and peptides, particularly insulin, have been developed. Here, chitosan‐conjugated undecylenic acid‐modified thermally hydrocarbonized porous silicon nanoparticles (CSUn NPs) are used, which promote the mucoadhesion and cellular interactions, thus boosting the intestinal permeability of insulin. Then, to further potentiate the mucoadhesion and permeability enhancement of chitosan‐modified NPs, the surface of the NPs is further modified with eitherl ‐cysteine (CYS‐CSUn NPs) or a cell‐penetrating peptide (CPP‐CSUn NPs). CYS‐CSUn and CPP‐CSUn NPs show 17‐ and 12‐fold increase in the apparent permeability of insulin across cellular intestinal cells, respectively, with significant enhancement in the cellular interactions. The insulin uptake mechanism pathways in intestinal cells from the developed NPs are also unraveled, which demonstrates major involvement of active transport process and electrostatic interactions, along with adsorptive and clathrin‐mediated endocytic pathways. Moreover, after oral administration in diabetic rats, CYS‐CSUn NPs show 1.86‐ and 2.03‐fold increase in the relative bioavailability of insulin, as compared to empty NPs and oral insulin solution, respectively. In conclusion, this study presentsl ‐cysteine modified CSUn NPs as a promising strategy with the ability to overcome the multiple barriers for oral delivery of insulin. Abstract : l ‐cysteine‐ and cell‐penetrating‐peptide‐modified, chitosan‐conjugated porous silicon nanoparticles (NPs) are developed for oral delivery of insulin. The NPs site‐specifically deliver insulin in the intestine where it associate with the mucus layers and come in close proximity to the intestinal epithelia where enhances its permeation across the intestine wall.